Advancing translational research with next‐generation protein microarrays. Issue 8 (31st March 2016) - Yu, Xiaobo; Petritis, Brianne; LaBaer, Joshua
Abstract : Protein microarrays are a high‐throughput technology used increasingly in translational research, seeking to apply basic science findings to enhance human health. In addition to assessing protein levels, posttranslational modifications, and signaling pathways in patient samples, protein microarrays have aided in the identification of potential protein biomarkers of disease and infection. In this perspective, the different types of full‐length protein microarrays that are used in translational research are reviewed. Specific studies employing these microarrays are presented to highlight their potential in finding solutions to real clinical problems. Finally, the criteria that should be considered when developing next‐generation protein microarrays are provided.